Design of an expandable junk catcher - Olsen, Kim A. (UiT Norges arktiske universitet, 2017)
"This report describes phase I of the project ""Design of an expandable junk catcher"", which is carried out on behalf of Qinterra Technologies, Department of Plugs & Packers in Narvik, as a part of the subject SHO6263 Diploma thesis M-ID. The main purpose of the project is to develop a new type of well intervention equipment to solve the problem of unwanted residue from debris on temporary installed downhole tools. Debris often consists of a mixture of sand, corrosion, scaling, oil, seawater, emulsions etc. The volume of sand and debris can be quite substantial and may cause severe problems, especially under the process of retrieving the tool from the well. Debris deposited on the tool may give trouble with the retrieval of the tool, and particles entering the mechanical parts of the tool may harm them. To reduce this problem, Junk catchers (JC) are being used to catch and collect the sand and debris before it settles on top of the installed tool. The junk catcher with collected debris is then pulled out of the well separately, leaving a clean working environment behind. The junk catchers in use by Qinterra today primarily consist of a rigid tube in which the sand/debris can be collected. This JC has a natural flaw in its design, because a part of the sand/debris will fall down in the annulus space between the junk catcher’s outer wall and the casing/tubing’s inner wall. Which leads to the possibility that sand/debris may still cause problems with the retrieval of the tools, even when the junk catcher is used. The primary objective of the project is to develop a new design for the junk catcher with the ability to seal the annulus space when the catcher is installed, to lower the risk of getting inflicted damage to other equipment due to debris. This would significally improve the performance of the catcher. In addition, the catcher need to be centralized in the casing/pipe/formation during or after installation is completed. The developed solution must not cause problems while running in the well or during ...